Christians, Jews, and Muslims in the medieval Mediterranean - Bird, Jessalynn L. (Brill's companions to the Christian tradition, 2026)
"The burgeoning field of Mediterranean Studies, which favors intersectionality over compartmentalisation, has resulted in fresh ways of understanding pre-modern interreligious relationships. This volume will introduce advanced students and non-specialists to various historical interactions between Christians, Jews, and Muslims within the frame of the "sea at the centre". Its chronological range is the long central Middle Ages (1000 to 1600 CE), and includes most Mediterranean regions: Iberia, North Africa, the Levant, Asia Minor, the Balkans, Italy, Provence, and the sea itself"-- Provided by publisher